Investigating the efficacy of universally delivered cognitive behaviour therapy in the promotion of emotional literacy and mental wellbeing with year 5 pupils - Brightmore, Alexandria (2016)
This study builds on existing research into the efficacy of universal Cognitive Behaviour Therapy (CBT) based programmes in schools in the promotion of Emotional Literacy and more broadly Mental Wellbeing. Previous research in this area has focused on CBT interventions delivered to targeted groups. In this instance, the focus was on CBT based universal, whole class intervention. The specific CBT intervention utilised the ‘Think Good Feel Good: A Cognitive Behaviour Therapy Workbook for Children and Young People’ (TGFG) resource (Stallard, 2002). The researcher was also able to take the opportunity to evaluate the possible additional impact of conducting CBT based interventions in parallel with the Social and Emotional Aspects of Learning (SEAL) programme. Initially, a pilot study was conducted with a single Year 5 child. The purpose of the pilot was to provide a guide as to the effectiveness of the resources to be used, to familiarise the researcher with those tools and principles of the study, and to provide meaningful feedback to aid in the fine tuning of the full research. The main research study was conducted in two schools within the local authority in which the researcher was a practising Trainee Educational Psychologist. Participants consisted of 85 Year 5 pupils (aged between 9 and 10). Measures were recorded before and following intervention using the Southampton Emotional Literacy Resource (SELR) and the Strength and Difficulties Questionnaire (SDQ). Data were collected from teachers, parents and the children. A fixed design was employed, with participants placed in one of three groups:  Experimental group 1 - One class (n=25) received CBT intervention alongside the SEAL programme over a 6 week period. The CBT intervention consisted of two one hour long sessions per week and was delivered by the researcher, with support from the relevant class teachers  Experimental group 2 - A second class (n=31) received only the CBT based intervention, for the same period and delivered in the same manner as with experimental group 1  Control group 3 - A group of 29 Year 5 pupils were also part of the study but received no intervention. Statistical analysis on the non-normally distributed dataset indicated that significant differences were found in some domains for experimental group 2 (CBT) compared to the control group (3). Further analysis indicated that these significant differences were as a result of positive change. Additionally, significant differences were found in some domains for experimental group 1 (SEAL + CBT) when compared with experimental group 2 (CBT alone). Further analysis indicated that these significant differences were as a result of negative change. The researcher suggests that the present study tentatively contributes to the growing evidence base for the potential effectiveness of CBT based interventions delivered within a universal framework regarding the promotion of emotional literacy and mental wellbeing. Findings lend some support for the use of CBT based interventions (i.e. the Think Good Feel Good resource) as part of the standard curriculum for Year 5 pupils, suggesting a possible positive impact on some areas of emotional literacy and more broadly mental wellbeing. Additionally, the study offers potential suggestions for future study along with implications and considerations for educational psychologists when undertaking therapeutic type work with children.